Goat Rearing and Rural Poor: A Case Study in South-western Semi-arid Zone of Uttar Pradesh - Kumar, Shalander; Deoghare, P R (Annals of Arid Zone, 2016)
The paper examines the role of goats in the economy of rural resourcepoor in India. It is observed from the field study conduct,e? in semi- rid parts of India that goats play a significant role in food and nutntlOnal secunty of the family of goat keepers. Goat rearing utilizes the labor, which has negligible opportunity , cost, and generates income and employment. Importantly, it helps in the empowerm nt of poor rural women by providing them employment and to some extent financIal autonomy. It was also observed that the goats of rural poor were mainly dependent ’on common property resources (CPRs), which have been declining in the recent past.